2017
DOI: 10.1097/mej.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Drug safety at admission to emergency department: an innovative model for PRIOritizing patients for MEdication Reconciliation (PRIOMER)

Abstract: This innovative prioritizing model is designed to be practical in the fast-paced workflow at the ED and can identify what patients are at increased risk of having crMDs. The multidisciplinary working model was proven time efficient and could contribute towards increased patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 167 publications
0
11
1
Order By: Relevance
“…Despite the presence of some study reports showing the association [ 2 , 21 , 23 ], binary logistic regression analysis did not show any potential relationship of age or sex with medication discrepancy in this study. Indeed, demographics of patients revealed comparable characteristics for sex and age (Table 1 ).…”
Section: Main Textcontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite the presence of some study reports showing the association [ 2 , 21 , 23 ], binary logistic regression analysis did not show any potential relationship of age or sex with medication discrepancy in this study. Indeed, demographics of patients revealed comparable characteristics for sex and age (Table 1 ).…”
Section: Main Textcontrasting
confidence: 99%
“…Various characteristics are highlighted to predict harmful discrepancies [ 21 ]. The number of medications received by a patient [ 18 , 22 ], older age, sex (woman), more frequent admission in the past 12 months and reason for patient admission were key predictors indicated in relation with potential harmful discrepancies [ 2 , 21 , 23 ]. In some studies, drug omission was reported as a frequent cause of unintended medication discrepancy [ 8 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This version of the risk-scoring tool included similar variables, with point allocation assigned based on clinical experience and consensus of the pharmacy team, taking into consideration similar scoring system studies. 17,18 For each patient, this risk score is calculated and categorized as low risk (0-39) or high risk (40+) for medication discrepancies. The score threshold was also set rather arbitrarily based on the distribution of patient scores and available pharmacy resources for obtaining a medication history for high-risk patients.…”
Section: Settingmentioning
confidence: 99%
“…At the time of tool creation, only two small studies seeking to identify patients in need of medication reconciliation were identified. 17,18 Due to this lack of evidence, the variables included in the scoring tool were primarily decided upon based on clinical experience and consensus of the team with consideration of the aforementioned two studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, drug-related admissions due to non-compliance or potential prescribing omissions were not recognized. [69]. Only prescribed drugs taken regularly were considered in this study; hence, SADEs that might have been related to over-thecounter drugs and drugs used as needed were not recorded.…”
Section: Strengths and Limitationsmentioning
confidence: 99%